KUALITAS PELAYANAN PEMBUATAN SURAT IZIN MENGEMUDI (SIM) ONLINE DI POLRES SLEMAN - Wakhyuni, Tri; Syakdiah, Syakdiah; Kusumawati, Retno (POPULIKA, 2020)
The SIM Online service is a program launched by the Indonesian National Police through the National Police Priority Program, namely Promoter. One of them from the program is information technology based services. Sleman Police Resort is one of the Polres being a pilot project in the DIY Regional Police jurisdiction in conducting Online SIM Services which is supported by the SIM Implementation Unit (Satpas). The delivery of public services must meet the service quality requirements in accordance with the objectives of the program. To measure service quality, the authors use service quality indicators, namely reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), and physical evidence (tangible).This study aims to examine and describe the quality of service making Online Driving License (SIM) at the Sleman Police Resort. The research method used is descriptive qualitative. Data collection techniques used were interviews, observation and documentation. Qualitative data analysis techniques are used to analyze the research data.Based on the results of the study, it was obtained that to measure the quality of Online SIM services at the Sleman Police Satpas using 5 (five) dimensions of service quality as follows; First, the Reliabilty dimension, has not been supported by all human resources who have competency certification in managing SIM Online, but there are already Standard Operating Procedures (SOPs) in the SIM Online service. Second, the Responsiveness dimension, the existence of a fast standard time in SIM extension only requires 15 minutes and for a New SIM requires between 75 minutes to 90 minutes according to the type of SIM. In addition to speed, the service is carried out appropriately with the existence of clear costs based on PP No. 60 of 2016. Third, the dimension of Assurance, the knowledge and abilities of Satpas officers in the SIM Online service. Constraints faced in providing online SIM service guarantees are difficult practice exams and many do not pass. Fourth, Empathy dimension, there is full attention and firmness in the presence of queue numbers and arrangements without any favoritism and discrimination in service in SIM Online services. Fifth, Tangible dimension, there is a Satpas building that has not been used optimally because it has only been used for practical tests, internet networks that are often down and offline, and the number of computers and other devices that are not yet proportional to the large number of people in the SIM Online service. While the information media and waiting room are good and complete.From these results it can be concluded that based on 5 (five) dimensions of service quality, in general it has gone well, but there are some things that need to be improved, such as the quality of human resources, optimization of Satpas buildings, addition of internet network bandwidth, addition of computers and review of regulations about practice exams.